Efficacy and safety of electroacupuncture for paralytic ileus in severe stroke: a protocol of multicenter, randomized controlled trial - Nie, Dehui; Zhang, Meiling; Han, Bin; Jin, Dan; Huang, Jianlong; Lu, Liming (Frontiers in Neurology, 2025)
IntroductionParalytic ileus is a frequent and serious complication of severe stroke, associated with poor prognosis and prolonged hospitalization. Current pharmacological options are limited by side effects and uncertain efficacy. Although electroacupuncture has shown promise in improving gastrointestinal motility, high-quality trials specifically targeting stroke-related paralytic ileus are still lacking, leaving an important evidence gap.MethodsThis multicenter randomized controlled trial will recruit at least 100 severe stroke patients with paralytic ileus across China. Participants will be randomly assigned (1:1) to an electroacupuncture or sham electroacupuncture group. The electroacupuncture group will receive standardized electroacupuncture, while the sham electroacupuncture group will undergo sham acupuncture without electrical stimulation. The primary outcome is weekly spontaneous bowel movements. Secondary outcomes include bowel movement regularity, abdominal circumference, bowel sounds, emergency medication use, Glasgow Coma Scale, National Institutes of Health Stroke Scale, Modified Rankin Scale and length of hospitalization. Adverse events will be systematically monitored and recorded throughout the study. Efficacy will be assessed using linear mixed-effects models or generalized linear mixed models, with both intention-to-treat and per-protocol analyses performed.DiscussionThe results of this multicenter RCT will provide robust evidence on the efficacy and safety of electroacupuncture for stroke-related paralytic ileus and may inform future clinical practice and guideline development.Clinical trial registrationhttps://itmctr.ccebtcm.org.cn/, identifier ITMCTR2025000003.